INTEGRASI HUKUM KEWARISAN ISLAM DAN KEARIFAN LOKAL DALAM PENYELESAIAN SENGKETA WARIS BERBASIS MUSYAWARAH ADAT (STUDI KASUS DESA SIMPANG SARI KECAMATAN LAWANG WETAN KABUPATEN MUSI BANYUASIN) - Ariansyah, Jeri (LPPM STAI Muhammadiyah Probolinggo, 2025)
The increasing occurrence of inheritance disputes in rural communities, particularly in Simpang Sari Village, often triggers family conflicts and affects social relations. This is largely due to the the community's lack of knowledge regarding Islamic inheritance law and a lack of understanding of the applicable inheritance regulations, including statutory law, Islamic law, and customary law. This study aims to examine how Islamic inheritance law is applied in resolving inheritance disputes and how it is integrated with the local wisdom that has developed within the community. A qualitative research method with a descriptive approach was employed, using interviews, observations, and document analysis. The research informants included religious leaders, traditional leaders, village officials, and individuals who have been directly involved in inheritance disputes. The findings indicate that while Islamic inheritance law is acknowledged and respected, the practical resolution of disputes prioritizes values of local wisdom, such as deliberation, consensus, and a family-oriented approach. In conclusion, Islamic inheritance law can be effectively applied in resolving inheritance disputes in Simpang Sari Village; however, it must be implemented alongside local wisdom that has been passed down through generations, taking into account customary practices, family harmony, and deliberative decision-making.